AKUNTABILITAS DALAM PERSPEKTIF TEORI AGENSI - Kholmi, Masiyah (Journal of Innovation in Business and Economics, 2011)
Accountability is an inseparable part of  agency theoryabout  the relationship between agent (management) and principal (owner). The essence of theory, difficult creation of relationship between owners and management because conflict of interest. The Solution to improve  the performance-based compensation is to give a  reward to agent in order to optimizing their work. To maintain accountability, agent is obliged to act in the interests of the principal and the principal gives the power to recognizes agents performance  or give a punishment to them.